Stakeholder Relationships in the Framework of R&D-based Startups: Evidence from Turkey - Elif Kalayci (Foresight and STI Governance, 2017)
It is widely acknowledged that R&D based startups play a significant role in the economic growth of many countries. However, founding such an enterprise is a risky endeavor, one that requires a balance between the technological search process and business capabilities. Most of the time these varied skills are found among several different people. The task becomes more difficult for recent engineering school graduates who are neither scientists nor business people. Therefore, it is critical for these new techno-entrepreneurs to conscientiously work on building relationships with stakeholders through whom they might access scientific knowledge on one hand and commercial knowledge on the other.The paper explores the process of building relationships with stakeholders based on evidence from Turkish companies. It begins with a review of literature, presenting the different theories concerning relationships with stakeholders as far as entrepreneurship is concerned. Then, it presents the methodology, classification and analysis of in-depth interviews with the founders of R&D-based startups, which help justify the use of a qualitative approach. The case profiles are considered with a focus on the following issues: the counterbalancing of stakeholder power, learning by the entrepreneur as a by-product of interactions with stakeholders, and the earning of a reputation through ethical and passionate business practices. Building upon these preliminary findings, the author draws three main propositions that could be the subject of further research.The main finding of this paper is that there are two opposing forces affecting the development of any company — problem and supporter stakeholders. At that, a stakeholder who was once a supporter could turn into a challenger or vice versa. The entrepreneur could benefit from the counterbalancing effect of these forces. Two major stakeholder groups emerged at the initial stage of the business: the family members and the state’s grant-handling officers. Then, the ethical and passionate conduct of business by these startups could become a factor drawing third parties in to become stakeholders of these startups. The nature and impact of these relationships should be researched further. Such an analysis allows one to understand how R&D-based startups are established and what kind of problems they face when turning (hopefully) into large corporations. On such a basis, this could help governments develop more suitable support programs that would benefit and expand the opportunities available to the founders of new R&D-based firms.